Ruminal methane emissions in grazing beef heifers. - PIOTTO, V. C. (2016)
Brazil is one of the largest beef exporter in the world, and this is due to the introduction of Nellore cattle which has been adapted to the edaphoclimatic conditions of the country. With more than 200 million head, distributed in different production managements, producing through mainly extensive grazing system, Brazil has the responsibility to increase its productivity. That means, to produce more in smaller areas using fewer animals. One option to achieve that goal is to make the rotational management, thus, it may provide a better control of food supply for animals. However, it is also necessary to be concerned about the environment, especially for the methane produced from enteric fermentation in rumen. The objective of this study was to measure the emission of enteric methane in beef heifers in rotational and continuous grazing systems.